Local injection of leukocyte rich platelet rich plasma produced higher radius union scoring system than local injection of pure platelet rich plasma in conservative therapy of intra-articular closed distal radius fractures - Sunaria, I. Made; Dusak, I Wayan Suryanto; Wiratnaya, I. Gede Eka (International Journal of Research in Medical Sciences, 2021)
Background: Distal radius fracture often occurs both extra-articular and intra-articular, covering all ages. The use of autologous platelet rich plasma (PRP) consisting of leucocytes rich-PRP (L-PRP) and pure-PRP (P-PRP) thought can help in bone healing process. This study aimed to determine that the administration of L-PRP provides a better healing rate than P-PRP in intra-articular closed distal radius fractures after conservative treatment. Methods: This was a single-blinded experimental study with stratified randomized post-test only group design involving 51 patients with closed distal fractures undergoing closed reduction, consisting of 17 patients per study group. Group 1 received placebo, group 2 received P-PRP, and group 3 with L-PRP. Each group was then re-evaluated using x-ray at week 2, 3, and 6. RUSS score was then measured. Data was analysed using descriptive statistics and normality test, homogeneity test and inferential test were performed to determine the effect of L-PRP, P-PRP on the union rate of fracture distal radius. All obtained data was analysed using SPSS statistics 22 software. Results: Between control and P-PRP group, there was significant difference in mean RUSS with p value of 0.012. Between control and L-PRP injection group, there was a significant difference in mean RUSS with p value of 0.000. Between P-PRP and L-PRP group, there was also significant mean RUSS difference with p value of 0.003. Conclusions: There was a significant difference between the control group given placebo and the group P-PRP and L-PRP in closed fractures of the intraarticular radius after conservative therapy.